2002
DOI: 10.1182/blood.v99.6.2045
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived growth factor inhibits basic fibroblast growth factor angiogenic properties in vitro and in vivo through its α receptor

Abstract: Basic fibroblast growth factor (bFGF) and platelet-derived growth factor-BB (PDGF-BB) modulate vascular wall cell function in vitro and angiogenesis in vivo. The aim of the current study was to determine how bovine aorta endothelial cells (BAECs) respond to the simultaneous exposure to PDGF-BB and bFGF. It was found that bFGF-dependent BAEC migration, proliferation, and differentiation into tubelike structures on reconstituted extracellular matrix (Matrigel) were inhibited by PDGF-BB. The role played by PDGF r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 64 publications
5
47
0
2
Order By: Relevance
“…This interaction may contribute to the inhibitory effect exerted by PDGF-BB on FGF2-dependent neovascularization [169].…”
Section: Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…This interaction may contribute to the inhibitory effect exerted by PDGF-BB on FGF2-dependent neovascularization [169].…”
Section: Cytokinesmentioning
confidence: 99%
“…Since then, 22 structurally-related members of the FGF family have been identified [8]. FGFs are pleiotropic factors acting on different cell types, including www.elsevier.com/locate/cytogfr Cytokine & Growth Factor Reviews 16 (2005) [159][160][161][162][163][164][165][166][167][168][169][170][171][172][173][174][175][176][177][178] endothelial cells, following interaction with heparan-sulfate proteoglycans (HSPGs) and tyrosine kinase FGF receptors (FGFRs). To date, more than 1200 PubMed-referenced papers related to FGFs and FGFRs in endothelial cells and during neovascularization have been published.…”
Section: Introductionmentioning
confidence: 99%
“…These data agree with previous observations collected on bovine aorta endothelial cells. 13 The following experiments were then carried out to identify at which level PDGF-BB exerts its modulating effects on FGF-2. Signaling molecules located at different levels onto the FGF-2 signaling pathway were analyzed.…”
Section: Pdgf-bb Inhibits Fgf-2-induced Huvec Proliferation and Intramentioning
confidence: 99%
“…8 Although the PDGF family is known to exert mitogenic and chemotactic action, PDGF-AA and PDGF-R␣ are less potent or even inhibitory molecules on endothelial and vascular cells, as we and others have shown. [9][10][11][12][13] We have previously observed a direct in vitro high-affinity FGF-2/PDGF-BB interaction 14 and strong FGF-2 inhibition both in vitro and in vivo in the presence of either PDGF-BB or PDGF-AA, through a PDGF-R␣-mediated mechanism. 13 Consistent with these data, other groups have shown that PDGF-R␣ may activate positive and negative signals 15 mediated by JNK-1 and p21WAF/CIP1 promoter induction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation